2007
DOI: 10.1536/ihj.48.269
|View full text |Cite
|
Sign up to set email alerts
|

Massive Pulmonary Thromboembolism in Pregnancy Rescued Using Transcatheter Thrombectomy

Abstract: SUMMARYWe report a rescued 37-year-old woman in her 30 th week of gestation with massive pulmonary thromboembolism who was admitted to our cardiac care unit with progressive dyspnea and 2 episodes of syncope. Helical chest CT showed massive pulmonary thromboembolism of both pulmonary arteries. Although 26,000 U/day of heparin was administered following insertion of a temporary filter, hemodynamic evaluation documented no improvement. Since pulmonary artery (PA) pressure increased from 62/22 mmHg to 80/ 24 mmHg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 22 publications
0
16
0
3
Order By: Relevance
“…Excluding one case with major bleeding during the surgical embolectomy that followed the percutaneous fragmentation and one case without information, the risk of major bleeding related to percutaneous catheter thrombectomy was 20.0% (1/5; 95% CI, 1–72). The risk of fetal death among antenatal cases (excluding one case with CS prior to thrombectomy ) was 25.0% (1/4; 95% CI, 1–81).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excluding one case with major bleeding during the surgical embolectomy that followed the percutaneous fragmentation and one case without information, the risk of major bleeding related to percutaneous catheter thrombectomy was 20.0% (1/5; 95% CI, 1–72). The risk of fetal death among antenatal cases (excluding one case with CS prior to thrombectomy ) was 25.0% (1/4; 95% CI, 1–81).…”
Section: Resultsmentioning
confidence: 99%
“…We found seven cases of severe PE treated with percutaneous fragmentation or thromboaspiration without thrombolysis (six massive PEs and one of uncertain severity; Table 2 and Table S2). Five had a diagnosis of PE before delivery [20,[37][38][39][40] and two in the early postpartum period [41,42]. Procedures were thrombus aspiration, fragmentation of thrombi by catheter or rheolytic thrombectomies.…”
Section: Percutaneous Catheter Thrombectomymentioning
confidence: 99%
“…In case of massive critical PE (the lesion area of the pulmonary vascular bed is more than 70%) with the development of severe cardiopulmonary insufficiency and high risk of death one considers possibilities of thrombolytic therapy, selective intra-arterial thrombolysis with destruction and aspiration of thromboemboli as well as open embolectomy. The publications analyzing these variants of treatment provide mainly a series of descriptions of clinical observations [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Sakai et al 9) reported that aspiration thrombectomy removed a massive thrombus from the native coronary artery of a patient with myocardial infarction, and this achieved successful reperfusion. Sato et al 10) reported that a massive pulmonary thromboembolism in a pregnant woman, and she was treated with transcatheter thrombectomy and the patient's hemodynamics recovered dramatically.…”
Section: Discussionmentioning
confidence: 99%